Investigation of 115 kV capacitor bank failure during switching in Chiang Mai 3 substation - Sarawut Kanitpanyacharoen (2018)
In this contribution, the investigation on the failures of 115-kV capacitor banks during switching in Chiang Mai 3 substation is presented. The switching transient is caused by energizing an isolated bank and back-to-back switching. Close time of circuit breaker for energizing capacitor bank, system loads, and power factors are varied in the simulations by PSCAD/EMTDC program to determine the causes of maximum inrush current and overvoltage. Simulation results of energizing isolated bank suggest that the maximum inrush currents occurs with a higher system load while the maximum overvoltage occurs in a lower system load. The back-to-back switching sequence of capacitor banks has given different results. Method No.1 is the most optimal sequence for energizing capacitor bank and is most likely to minimize the effects of back-to-back switching. © 2011 IEEE.